"Żyd wieczny tułacz", czyli średniowieczna legenda w epoce powieści w odcinkach = Eugene Sue`s "The Wandering Jew" - From a?Medieval Legend to a Serialized Novel - Kallas, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper undertakes the study of Eugene Sue`s famous serialized novel in the context of the historyof the Legend of the Wandering Jew. The Legend itself, of a medieval origin, was very popular withRomantic writers in several western European countries, especially in Britain, France and Germany.Contrary to what one might expect, Eugene Sue`s title character plays a relatively minor role inthe story.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); literatura francuska - historia - 19 w.; powieść francuska - 19 w.